1985
DOI: 10.1002/jemt.1060020204
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde fixatives: Quantification of acid‐producing reactions

Abstract: Under conditions commonly used for the preservation of tissue for electron microscopy, substantial amounts of hydrogen ions were produced when either formaldehyde or glutaraldehyde was added to solutions of amines or proteins, or to tissue homogenates. In glycine-aldehyde reactions, hydrogen ions were generated in linear proportion to the glycine concentration over the range of 0.001 M to 0.100 M glycine. In the presence of 1% formaldehyde or 1% glutaraldehyde, 0.3-0.9 equivalents of acid were produced per mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Hence it is unclear if exposure of ultrathin cryosections to an acidic milieu reverses such crosslinks and to what extent, if at all. It has been shown that the ratio of the glutaraldehyde concentration to the amine concentration determines various aspects of the fixation process, e.g., the nature of the products formed (Johnson 1985). On this point, the glutaraldehyde concentration of 0.1% in our fixative was rather low.…”
Section: Resultsmentioning
confidence: 75%
“…Hence it is unclear if exposure of ultrathin cryosections to an acidic milieu reverses such crosslinks and to what extent, if at all. It has been shown that the ratio of the glutaraldehyde concentration to the amine concentration determines various aspects of the fixation process, e.g., the nature of the products formed (Johnson 1985). On this point, the glutaraldehyde concentration of 0.1% in our fixative was rather low.…”
Section: Resultsmentioning
confidence: 75%
“…The released protons will be partially neutralized by the inherent buffering capacity of cytoplasmic components, although this capacity is relatively low [31]. No effect of formaldehyde on pH was observed during the in vitro mitochondrial binding reactions.…”
Section: Proton Release With Formaldehydementioning
confidence: 98%
“…It is known, but generally unappreciated that fixation with aldehydes causes the release of protons, primarily derived from the reaction with primary amines [31,32]. The released protons will be partially neutralized by the inherent buffering capacity of cytoplasmic components, although this capacity is relatively low [31].…”
Section: Proton Release With Formaldehydementioning
confidence: 99%
“…(This may mean that surface fibers are exposed to high concentrations of glutaraldehyde more quickly than are the fibers in perfusion-fixed muscle, where diffusion from the restricted volume of the capillary bed may delay fixation for several additional seconds and expose the fiber to slowly increasing concentration of fixative.) There also appear to be other aspects of fixation chemistry influencing these reported changes (i.e., hypoxia, acid production, and/or loss of positive charges on membranes (Johnson, 1985(Johnson, , 1986. Moreover, the current and previous data (Lee et al, 1986) raise additional concerns (Chandler and Heuser, 1979) as to the extent different chemical fixation methods induce artifactual changes in the morphology of other (membranous and cytoplasmic) structures.…”
Section: Discussionmentioning
confidence: 99%